HUBUNGAN TEMAN SEBAYA (PEER GROUP) DAN TINGKAT PENGETAHUAN DENGAN KEBIASAAN KONSUMSI JUNK FOOD DI SMA NEGERI 21 MAKASSAR: RELATIONSHIP BETWEEN OF PEER GROUP AND LEVEL KNOWLEDGE WITH JUNK FOOD CONSUMPTION HABITS IN ADOLESCENTS AT SENIOR HIGH SCHOOL 21 MAKASSAR - Rahmah, Ainun; Amir, Safrullah; Hasan, Nurzakiah (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2025)
Bakground. Adolescents are a group that is vulnerable to nutritional problems due to unbalanced eating habits such as junk food. Junk food consumption has increased in all age groups and mostly occurs among young adults with a global prevalence of around 70%. Many factors influence junk food consumption in adolescents such as peer group influence and level of knowledge. Objective. To determine the relationship between peer group and level of knowledge with junk food (JF) consumption habits in adolescents. Method. This research is an analytical observational with a cross-sectional design. The sample was obtained using proportional random sampling technique of 143 adolescents. The research instruments used the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), peer group questionnaires, and knowledge questionnaires. Data analysis used chi-square test. Result. Based on the research results, it was found that 62.2% of adolescents were influenced by their peer group in consuming JF. 50,3% of adolescents have a good level of knowledge about JF. The statistical test results showed that there was no significant relationship between the peer group and the amount of JF consumed (p-value=0.312) and the peer group and the frequency of JF consumption (p-value=0.401). There is a significant relationship between the level of knowledge and the amount of JF consumed (p-value=<0.001), and the level of knowledge and the frequency of JF consumption (p-value=0.002). Conclusion and Recommendations. Adolescents' knowledge level is significantly related to their consumption of junk food. There needs to be further efforts to increase knowledge of junk food among adolescents.